All equations the the form ax^2+bx+c=0 have the right to be addressed using the quadratic formula: \frac-b±\sqrtb^2-4ac2a. The quadratic formula gives two solutions, one once ± is addition and one as soon as it is subtraction.

You are watching: 9x^2-12x+4=0


This equation is in conventional form: ax^2+bx+c=0. Instead of 9 for a, -12 for b, and also -4 for c in the quadratic formula, \frac-b±\sqrtb^2-4ac2a.
*

9x2-12x-14=0 Two remedies were discovered : x =(12-√648)/18=2/3-√ 2 = -0.748 x =(12+√648)/18=2/3+√ 2 = 2.081 step by action solution : step 1 :Equation at the finish of step 1 : (32x2 - 12x) - 14 ...
9x2-12x-24=0 Two services were uncovered : x =(4-√112)/6=(2-2√ 7 )/3= -1.097 x =(4+√112)/6=(2+2√ 7 )/3= 2.431 action by step solution : action 1 :Equation at the end of action 1 : (32x2 - 12x) - ...
3x2-12x-4=0 Two solutions were found : x =(12-√192)/6=2-4/3√ 3 = -0.309 x =(12+√192)/6=2+4/3√ 3 = 4.309 step by action solution : action 1 :Equation in ~ the end of action 1 : (3x2 - 12x) - 4 = 0 ...
7x2-12x-4=0 Two solutions were uncovered : x = -2/7 = -0.286 x = 2 step by step solution : step 1 :Equation at the end of action 1 : (7x2 - 12x) - 4 = 0 step 2 :Trying to factor by separating ...
x2-12x-14=0 Two solutions were discovered : x =(12-√200)/2=6-5√ 2 = -1.071 x =(12+√200)/2=6+5√ 2 = 13.071 step by step solution : action 1 :Trying to variable by splitting the middle term ...
x2-12x-45=0 Two options were discovered : x = 15 x = -3 step by action solution : step 1 :Trying to aspect by dividing the middle term 1.1 Factoring x2-12x-45 The first term is, x2 that is ...
More Items
*
*

*
*
*

All equations of the form ax^2+bx+c=0 can be addressed using the quadratic formula: \frac-b±\sqrtb^2-4ac2a. The quadratic formula provides two solutions, one as soon as ± is enhancement and one when it is subtraction.
This equation is in traditional form: ax^2+bx+c=0. Substitute 9 because that a, -12 because that b, and -4 for c in the quadratic formula, \frac-b±\sqrtb^2-4ac2a.
Quadratic equations such together this one can be solved by completing the square. In order to complete the square, the equation must an initial be in the type x^2+bx=c.

See more: Is A Light Switch A Lever Switch And What Uses Do They Have In Cars?


Divide -\frac43, the coefficient of the x term, through 2 to obtain -\frac23. Then include the square the -\frac23 to both political parties of the equation. This step renders the left hand side of the equation a perfect square.
*
*